Adolescent Illicit Drug Use and Policy Options in Australia: A Multicriteria Decision Analysis. (October 2017) - Wong, Gabriel T. W.; Manning, Matthew
The etiology of illicit substance involvement is a multidimensional problem shaped by factors across individual, social, and environmental domains. In this study, a multicriteria framework is employed to incorporate the input of specialists regarding risk and protective factors and the effectiveness of alternative interventions to mitigate the adverse harms and consequences associated with adolescent drug initiation and subsequent use. Using a seven-stage drug use continuum (nonuse, priming, initial use, experimental use, occasional use, regular use, and dysfunctional use), experts rate social and environmental factors as the most important from nonuse to occasional use. Experts often support preventive and harm-minimizing strategies to interrupt the progression of drug involvement and accumulation of drug-related harms among adolescents. Compared with preferable interventions, less preferable options (e.g., drug testing/monitoring) are considered to have a negative policy impact on key social, environmental, and drug dimension domains, which tend to override their positive impacts on other areas.